EDCRAN: an enhanced dual-channel residual attention network for real-time DDoS attack detection in IoT - Almazroi,Abdulaleem Ali (PeerJ Computer Science, 2026)
Cybersecurity is becoming important in healthcare, transportation, and urban infrastructure due to the increased implementation of Internet of Things (IoT) technology. Distribution Denial of Service (DDoS) attacks, which use IoT edge devices’ limited capacity to iterrupt systems, are a major issue. Scalability issues, ineffective feature extraction, and high computing overhead make traditional Intrusion Detection Systems (IDS) unsuitable for real-time operation on restricted devices. Enhanced Dual Channel Residual Attention Network (EDCRAN), a deep learning architecture for accurate and efficient DDoS detection, is introduced in this study to solve these constraints. The Transform Attention Channel (TAC) catches global temporal patterns in network data, whereas the Scaled Convolutional Channel (SCC) focusses on localised, context-aware characteristics. The model learns rich and discriminative representations from varied traffic sources using this dual-channel technique. To address class imbalance, a Dynamic Weighted Balancing Strategy (DWBS) adjusts learning contributions across classes, while Selective Hybrid Extraction (SHE) filters irrelevant features to improve generalisation. Offline tuning with the Golden Jackal Optimisation (GJO) method produces a lightweight model for IoT edge devices. In the IN-DDoS24 dataset, EDCRAN outperforms fifteen benchmark models with 98.9% accuracy, 99.5% AUC, and 22 s inference time. To assess temporal consistency and attack resilience, two new metrics CPS and ACWS are provided. The realistic, scalable EDCRAN solution detects DDoS in real time in next-generation IoT environments.
Keywords: DDOS attack; Deep learning; Cyber security; Internet of things